The Success of Shopping Malls Lies in the Hands of Mall Developers: A Study - Mullick, N. H. (Indian Journal of Marketing, 2013)
In India, out of the 12 million sq.ft of Indian shopping centre space planned for opening in 2012, only about 60 percent was expected to be complete (JLLS) because of the huge delay in mall projects in India's biggest cities. There is a stress even in the business model as it is getting a bit expensive. Real estate prices and construction costs are rising, but the retail business is not growing enough to absorb these costs. Retail rents are down by 30 to 40 percent as compared to the peak of 2008 (CRISIL). Shopping malls, therefore, cannot mushroom without analyzing the basics like the catchment area, the spending power of the demography, and its business potential. The malls have to be situated in places where there is scope for shopping. Innovation is, therefore, necessary and the retailers must be encouraged to enhance their diversity of services, and food and entertainment options must be encouraged rather than enhancing the size of the mall/retailer engagement. Better mall management must create ambience and a hygienic and a clean environment must be created for family members to enhance the loyalty of the consumers. The present study is based on the multiple drivers of growth and the issues being faced today by these shopping malls when more are coming up, but they are not able to find the right rentals, nor the required footfalls. A total marketing effort has to be made by these upcoming mall developers to make their ventures a success.